Between the physical and the virtual: The present tense of virtual space. Issue 1 (1st June 2021) - Burrell, Andrew
This article explores a way of thinking about virtual environments and how they might be used to create new spaces, not as an alternate reality, but as an integrated part of reality ‐ regardless of this reality being physical and/or digital. Virtual environments can be seen as an extension of reality ‐ the physical and the virtual sitting side by side with one, more often than not, bleeding into the other. The virtual is not separable from the physical and vice versa. This position will be formed by directly referring to traditions that stem from processes and ideas around materiality, poetics and philosophy rather than centring on technical or hardware specifics. At the centre of this exploration is an ongoing investigation into the role of memory and imagination in narrative spaces in immersive virtual environments, stemming from the author's background in interactive Installation art and designing for virtual environments. The article's subtitle refers to Robert Morris's 1978 article, 'The present tense of space', which informs the article's overall position.